2014
DOI: 10.3390/su6052392
|View full text |Cite
|
Sign up to set email alerts
|

A Point Source of a Different Color: Identifying a Gap in United States Regulatory Policy for “Green” CSO Treatment Using Constructed Wetlands

Abstract: Up to 850 billion gallons of untreated combined sewer overflow (CSO) is discharged into waters of the United States each year. Recent changes in CSO management policy support green infrastructure (GI) technologies as "front of the pipe" approaches to discharge mitigation by detention/reduction of urban stormwater runoff. Constructed wetlands for CSO treatment have been considered among suites of GI solutions. However, these wetlands differ fundamentally from other GI technologies in that they are "end of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Numerous studies have found that GI is actually cheaper than traditional grey infrastructure (Levy et al 2014;Li et al 2017;Tayouga and Gagn e 2016;Wild, Henneberry, and Gill 2017). A study by Yang et al (2015) measured the performance goal of retaining 100% of stormwater on-site and found savings of $40 million USD in stormwater infrastructure using GI strategies in Daybreak, Utah.…”
Section: Challenge #4: Financeabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have found that GI is actually cheaper than traditional grey infrastructure (Levy et al 2014;Li et al 2017;Tayouga and Gagn e 2016;Wild, Henneberry, and Gill 2017). A study by Yang et al (2015) measured the performance goal of retaining 100% of stormwater on-site and found savings of $40 million USD in stormwater infrastructure using GI strategies in Daybreak, Utah.…”
Section: Challenge #4: Financeabilitymentioning
confidence: 99%
“…Although GI may be cheaper, regulations may offset this economic advantage, particularly when the design parameters have not been institutionalized. In a cost-benefit analysis, Levy et al (2014) found that although constructed wetlands are the most economical solution to stormwater management in the United States, regulations that mandate water quality goals may hinder this economic advantage. Constructed wetlands, the authors explain, are a GI technology at the "end of the pipe" (p. 6) and therefore considered a point source for discharge; and this condition puts constructed wetlands under the US National Pollution Discharge Elimination Systems regulations.…”
Section: Challenge #4: Financeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The secondary services have been frequently cited to support inclusion of CWs in long-term CSO control plans [13,14]. Nevertheless, the value of secondary ecosystem services such as aesthetic quality and wildlife habitat in urban communities has not been quantified yet [5,25].…”
Section: Benefits Demonstrated By Existing Cso Constructed Wetlandsmentioning
confidence: 99%
“…This CSO wetland treatment system is permitted as two outfalls (#501 and #502) of the Akron Municipal Wastewater Treatment Plant by NPDES Permit IN0025232 [8]. The CSO discharges from two CSO points undergo grit and floatable removal in swirl separators, which then flow through two serpentine earthen FWS wetlands [5]. There are rock filtration structures at the inlet and outlet of the wetlands to help remove debris [18].…”
Section: Akron Cso Constructed Wetlands In Town Of Akron Indianamentioning
confidence: 99%